Feasibility of smartphone-enabled asynchronous video directly observed therapy to improve viral suppression outcomes among HIV unsuppressed children and adolescents in Kenya - Paul Wekesa; Margaret Ndisha; Boniface Makone; Marc Bulterys; Evelyn Ngugi; Kevin Kamenwa; Abraham Katana; Kevin Owuor; Immaculate Mutisya (BMC Infectious Diseases)
Abstract Background Video directly observed therapy (VDOT) has been used as an acceptable, cost-effective, client-centered intervention for tuberculosis management. VDOT targeting children (0–14 years) and adolescents (15–19 years) living with HIV (CALHIV) not achieving viral suppression (VS) [i.e., < 1000 copies/ml] was piloted in 73 facilities in Kenya. We conducted a feasibility study on the utilization and re-suppression rates of clients enrolled in VDOT. Methods A review of data from 223 virally unsuppressed clients aged between 0–19 years on antiretroviral therapy (ART) who were enrolled to use the VDOT application daily for at least 12 weeks between February 2021 and October 2022 at 73 health facilities was conducted. Clients stopped using the application upon achieving VS. VS was assessed after at least 12 weeks of VDOT follow-up through self-care or healthcare worker (HCW)-led approaches. Using a multivariable Cox Proportional Hazards regression model, we assessed demographic and clinical determinants of VS presenting adjusted hazard ratios (aHR). Results Most users, 163 (73.1%) were adolescents aged 10–19 years. Only 19 (8.5%) were on self-care VDOT. Median time on follow-up was 19 weeks, with 126 videos uploaded, and 75% VDOT adherence. Over three-fourths, 176 (78.9%) had achieved VS during follow-up. Results showed a higher likelihood of VS among children on once-daily compared to twice-daily ARV dosage, aHR = 2.51 (95% CI: 2.06 – 3.05), and those on second- or third-line regimens compared to those on first-line regimens, aHR = 3.05 (95% CI: 1.78 – 5.22). Similarly, those on a DTG-based regimen had a higher likelihood of VS compared to those on LPV/r-based, ATV/s-based, or EFV-based regimens, aHR = 1.95 (95% CI: 1.25 – 3.06). Children receiving care from guardians and siblings had a higher likelihood of VS compared to those receiving care from parent caregivers, 1.61 (95% CI: 1.27—2.03), and 2.00 (95% CI: 1.12 – 3.57), respectively. Conclusion VDOT supported the achievement of VS among unsuppressed CALHIV on antiretroviral treatment and was significantly associated with dosage frequency, antiretroviral regimen, first- or second-line therapy, antiretroviral regimen classification, and type of caregiver. Findings suggest the utility of VDOT among unsuppressed CALHIV in resource-limited settings.